Orange fleshed sweet potato-rice bran flour: Optimization, proximate and amino acid composition for dough meal production - Ayo Olugbuyi; Ajibola Oyinloye; Kudirat Araoye; Oluwatosin Ariseloye (Journal of Agriculture and Food Research, 2024)
This study focuses on optimizing the proximate composition of dough meal made from blends of orange-fleshed sweet potato, defatted sesame, and rice bran flour. The utilization of these readily available local ingredients demonstrates significant potential for enhancing the nutritional value of staple foods. The research employs a systematic approach to determine the optimal proportions of these three flours, with the goal of achieving a balanced profile of essential nutrients. Parameters such as moisture, protein, fat, carbohydrate, and dietary fiber content were analyzed for the optimized blends. The observed ranges for moisture, ash, protein, fat, fiber, and carbohydrates in the flour samples were 0.99–3.31, 1.44 - 8.88, 6.25 - 13.97, 6.09 - 12.22, 2.22 - 5.00, and 66.22 - 77.21g/100g, respectively. The optimal blends were determined using response surface methodology software, with a focus on achieving high protein and fiber content. Functional, pasting, and amino acid composition analyses were performed on these optimum blends. In conclusion, the optimized flour blends of orange-fleshed sweet potato, defatted sesame, and rice bran present a viable alternative to conventional unripe plantain flour for dough meal production. This research bridges the gap between traditional staples and nutritional enrichment, offering potential solutions for addressing nutritional deficiencies and promoting sustainable dietary practices. The findings contribute to the development of innovative food formulations that cater to both nutritional needs and consumer preferences.